Sistem Aplikasi Presensi dengan Foto Selfie dan Koordinat GPS Menggunakan Framework Laravel dan Metode Waterfall - Suhanda Saputra (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
This research focuses on designing a system to overcome the problem of employee attendance when working outside the office area. The scope of this research includes designing and developing a comprehensive Android application that includes rules and information packages. The Waterfall development method is used to ensure a systematic and sequential approach throughout the system life cycle. The proposed system aims to provide presence information and can increase the ease and accuracy of employees in taking attendance when working outside the office area. Apart from taking attendance, employees also have access to various features through this application, including leave and sick leave, attendance history, late attendance and employee profiles. Apart from that, to access as an admin of this application, an admin can access the features in the application's web panel. In this case the admin can carry out monitoring, approve permits (leave) and illness, add employee data, add customer data, attendance location points and summarize attendance reports. The expected result of this research is the successful design and development of a robust, website-based employee attendance application system. This system will effectively assist employees in conducting attendance, providing real time and accurate information. The usability, functionality, and efficiency of the system will be evaluated, and user feedback will be collected to assess its effectiveness.